2015
DOI: 10.1177/0340035215570556
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly productivity of Arab librarians in Library and Information Science journals from 1981 to 2010

Abstract: Several studies discussed the characteristics of authors who published in Library and Information Science journals. Although none focused specifically on Arab librarians as authors, the current study attempts to reveal the scholarly contributions to library literature by Arab librarians. The study describes and analyses the journal research publications in Library and Information Science journals by professional librarians from 1981 to 2010. Single-author articles are found to be highly followed by two and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Consistent with Zakaria (2015) and Joswick (1999), the findings of this study found that most Arab authors (80.9 per cent) publishing in Emerald's LIS journals preferred to be single authors; co-authorship appears not much favoured by many of them. Sole authorship is the most straightforward in terms of whose work the article reflects and is highly desirable it seems (Hargittai, 2004).…”
supporting
confidence: 81%
“…Consistent with Zakaria (2015) and Joswick (1999), the findings of this study found that most Arab authors (80.9 per cent) publishing in Emerald's LIS journals preferred to be single authors; co-authorship appears not much favoured by many of them. Sole authorship is the most straightforward in terms of whose work the article reflects and is highly desirable it seems (Hargittai, 2004).…”
supporting
confidence: 81%
“…The analysis of the papers revealed that research on topics like IT applications in libraries, electronic information resources, LIS education, academic libraries, and information-seeking was the most popular. Zakaria (2015) reviewed LIS papers published between 1981 and 2010 in eight reputed Arabian (18 countries) LIS journals. The study found that the most popular research topic was librarianship, followed by information technology and technical services.…”
Section: The Gulf and The Arab Regionmentioning
confidence: 99%